Control of Motor-Generator Pair for Photovoltaic Power Grid Integration - Yingkun Zhou; Yongzhang Huang; Yujun Gu; Chenyang Li (CSEE Journal of Power and Energy Systems)
Photovoltaic power (PV) is integrated into the grid through power inverters. But the inverters lead PV to lose some of the characteristics of conventional power sources that are conducive to grid stability, such as reduced inertia, reactive power regulation capability, and fault ride-through capability. After introducing the power angle characteristics of a motor-generator pair (MGP) and reviewing MGP's existing control methods and PV's characteristics, this paper proposes a DC voltage feedback control method that can make MGP follow the fluctuations of a PV source. The proposal is studied experimentally, with the following results: (1) An MGP system can follow the power fluctuation of PV by using a DC voltage feedback control method. (2) Such feedback enables the PV to have a self-synchronization characteristic, which enables PV to actively contribute to the stability of the grid.